Successful Management of Adolescent Bupropion Overdose with Intravenous Lipid Emulsion Therapy - Bornstein, Kasha; Montrief, Tim; Anwar Parris, Mehruba (Journal of Pediatric Intensive Care, 2019)
Bupropion overdose in the pediatric setting poses significant potential for toxicity. We present the case of a 15-year-old female patient presenting with intentional bupropion overdose resulting in generalized tonic–clonic seizures, severe acidosis, vomiting, and tachycardia after ingestion of between 1,650 to 9,000 mg (24–133 mg/kg) of bupropion. The patient was admitted to pediatric intensive care unit (PICU) where toxicity was resolved promptly following administration of intravenous lipid emulsion (ILE) infusion. ILE is a first-line treatment for other forms of toxicity including unintended local anesthetic administration. ILE use is not a first-line treatment in this setting, but this case presents a positive subsequent patient outcome.
Keywords: Bupropion; Wellbutrin; lipid emulsion therapy; antidepressant; overdose